2014
DOI: 10.3926/jiem.907
|View full text |Cite
|
Sign up to set email alerts
|

Lean environmental management integration system for sustainability of ISO 14001:2004 standard implementation

Abstract: Abstract:Purpose: The purpose of this study is to present a model for integrating Lean Principles with ISO 14001 Environmental Management System. Design/methodology: To achieve the objective of the study, the methodology used in this study is based on preliminary literature review of ISO 14001 standards and Lean Principles as well as certain case reports from various proponents and authors of ISO 14001 and Lean as noted in various articles and journals and some books. Findings: The findings of this study are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…According to the results of this test, LM and the adoption of an ISO 14001-based EMS can be integrated and be a greater driving force promoting green practices due to the congruence between their principles and requirements. This conclusion agrees with the studies [21,22] that suggest an integrative effect between LM and ISO 14001. In consequence our research provides empirical support to those studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to the results of this test, LM and the adoption of an ISO 14001-based EMS can be integrated and be a greater driving force promoting green practices due to the congruence between their principles and requirements. This conclusion agrees with the studies [21,22] that suggest an integrative effect between LM and ISO 14001. In consequence our research provides empirical support to those studies.…”
Section: Discussionsupporting
confidence: 93%
“…Related studies [21,22] considered LM and ISO 14001 to be complementary and state that LM and ISO 14001 should be integrated to achieve synergies. Jabbour et al [67] show that the requirements of ISO 14001 related to waste elimination and equipment maintenance highly overlap with the principles of LM and, consequently, both approaches can be integrated to create synergies [23,68].…”
Section: The Influences Of Pressure To Adopt Green Practices and Iso mentioning
confidence: 99%
See 1 more Smart Citation
“…In another empirical study for furniture industry, Miller et al, (2010) concluded in the favor of increased overall operational performance through co-deployment of lean and sustainability [243]. Similar claims were made by Puvanasvaran et al, (2014) [271]. Furthermore, Canon reduced CO 2 emissions in their facilities through SERU (similar to lean's cellular manufacturing) implementation [272].…”
Section: Key Performance Indicators (Kpis) Constructmentioning
confidence: 81%
“…The core elements of lean philosophy could be linked to ISO 14001 in a joint Lean Environmental Management Integration System (LEMIS) model, the inputs and outputs of the model, and the expected outcomes (Puvanasvaran et al, 2014b). Same should be done in quantification of OEE by putting both of the high utilization of equipment as well as customer demand into consideration to minimize the inventory level as the main expected outcomes.…”
Section: Characteristics Of Equipment Utilization Without Consideratimentioning
confidence: 99%